2002
DOI: 10.1111/1540-6288.00008
|View full text |Cite
|
Sign up to set email alerts
|

Payment For Risk: Constant Beta Vs. Dual‐Beta Models

Abstract: Fama and French's (1992) assertion that investors receive premium payments for risk associated with the book value to market price (BE/ME) and size and not for holding beta risk has sparked a lively debate concerning risk factors that are priced in the market. Howton and Peterson (1998) use a dual-beta model to test the Fama and French conclusions. They conclude that the significant relationship between beta and returns depends on the use of the dual-beta model. This work, however, ignores the results reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
53
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 21 publications
16
53
1
Order By: Relevance
“…These results are persistent across all subsamples and are not dependent on the conditioning variable. They are in accordance with the findings of Pettengill (1995Pettengill ( , 2002 and the perception of beta as a risk factor.…”
Section: Cross-section Regression Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These results are persistent across all subsamples and are not dependent on the conditioning variable. They are in accordance with the findings of Pettengill (1995Pettengill ( , 2002 and the perception of beta as a risk factor.…”
Section: Cross-section Regression Resultssupporting
confidence: 92%
“…They argue that when the excess market return is negative, an inverse relationship between cross-sectional returns and risk factors should emerge, which is supported by Pettengill et al (1995Pettengill et al ( , 2002, Fletcher (1997Fletcher ( , 2000 and Schulte et al (2011). To account for timevarying asset behaviour, the Fama-MacBeth regressions are also conducted conditionally following Pettengill et al (1995Pettengill et al ( , 2002. where is a dummy variable equal to 1, when the excess market return in month m+1 is positive and 0 if the excess market return is negative .…”
Section: Cross-section Regressionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the variation within groups is small and the statistical power to reject the null of a flat beta-return relation is low. In a follow-up study, Pettengill et al (2002) showed that the cross-sectional return premium associated with firm size was also asymmetric: the size effect is much more pronounced in down markets. They argue that the common assumption that betas are the same in up and down markets leads to an underestimation of the size effect.…”
Section: The Size Effectmentioning
confidence: 99%